2014
DOI: 10.1177/1744987114523976
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the self-management behaviours performed by prostate cancer survivors: a systematic review of the evidence

Abstract: Purpose: Prostate cancer survivors are keen to engage as active partners in the management of their condition but have voiced a number of unmet support needs that make effective selfmanagement problematic. Identifying self-management behaviours and evaluating how selfmanagement changes over time may provide valuable insights into how men can be better supported to self-manage. Our systematic review aimed to identify the self-management behaviours for prostate cancer survivors and to evaluate whether these chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…This suggests that the variance in QoL and FoR attributable to these self‐management behaviours may have been accounted for by our covariates or may have been confounded by the presence of other self‐management behaviours with which they were highly correlated. In spite of this, extant research has demonstrated the importance of these behaviours in cancer self‐management . With this in mind, further research is needed to determine the extent to which these behaviours benefit cancer survivors across various stages of the cancer trajectory and/or in relation to other important outcomes (eg, 5‐year survival).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This suggests that the variance in QoL and FoR attributable to these self‐management behaviours may have been accounted for by our covariates or may have been confounded by the presence of other self‐management behaviours with which they were highly correlated. In spite of this, extant research has demonstrated the importance of these behaviours in cancer self‐management . With this in mind, further research is needed to determine the extent to which these behaviours benefit cancer survivors across various stages of the cancer trajectory and/or in relation to other important outcomes (eg, 5‐year survival).…”
Section: Discussionmentioning
confidence: 78%
“…In spite of this, extant research has demonstrated the importance of these behaviours in cancer self-management. 5,6,8 With this in mind, further research is needed to determine the extent to which these behaviours benefit cancer survivors across various stages of the cancer trajectory and/or in relation to other important outcomes (eg, 5-year survival). Furthermore, because of their potential shared variance with other variables, more refined measures of these selfmanagement behaviours may be required, which better capture the potential unique variance that they account for in relation to important outcomes for HNC survivors (and, potentially, in relation to other cancer types).…”
Section: Vivors Hypervigilance Is a Key Component In Conceptualisatimentioning
confidence: 99%
“…Specifically, the narrative synthesis undertook the following steps: data reduction (sub-group classification based on the levels of evidence and the review questions), data comparison (iterative process of making comparisons and identifying relationships) and finally, conclusion and verification (checking primary data sources for accuracy and confirmability). This process has been applied to several systematic reviews including prostate cancer 17,18 .…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The patient was advised of the potential side-effects and risks, and a supported self-management plan was developed in partnership to monitor response to medication and lifestyle advice to optimize quality of life (Paterson et al, 2014;Nursing and Midwifery Council, 2006a). Any adverse drug reaction (ADR) to these medications would be reported in the Yellow Card commission on human medicines published in the British National Formulary (BNF) (Joint Formulary Committee, 2016).…”
Section: Critically Appraise Current Issues and Non-medical Factors Imentioning
confidence: 99%